Seawater carbonate chemistry and coral-algal interactions in an acidified ocean - Lankes, Johann D; Page, Heather N; Quasunella, Amanda; Torkelson, Jaclyn F; Lemaire, Clöe; Nowicki, Robert J; Blasius, Lillia; Hall, Emily R (PANGAEA, 2025)
This study aimed to simulate the indirect interaction between pelagic Sargassum spp. and Acropora cervicornis coral fragments from the Florida Reef in current-day and future ocean pH conditions over the course of 70 days in a mesocosm experimental system. Measurements of coral growth and health via buoyant weight and Pulse Amplitude Modulated (PAM) fluorescence measurements reveal an unexpected coral-algal interaction. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from Figshare (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-03-18.
Keywords: Acropora cervicornis; Animalia; Benthic animals; Benthos; Chromista; Cnidaria; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Growth/Morphology; Laboratory experiment; Macroalgae; North Atlantic; Ochrophyta; Primary production/Photosynthesis; Sargassum sp.; Species interaction; Temperate